A STUDY OF THE CRISIS OF THAI SOCIETY FROM CASES OF VIOLATION OF THE FIVE PRECEPTS - Opaso (Nakrit), Phraopas; Yanameetee (kraithp), Phra Nattapong (Journal of MCU Nakhondhat, 2021)
The Objectives of this research article were to study the state of Thai social crisis from the violations of the Five Precepts and to study the causes of the Thai social crisis from the violation of the Five Precepts By studying from daily newspaper papers and interviews with ten key informants / person, who are experts in the state of the Thai social crisis from violations of the Five precepts. The research tool is news content form. Data analysis form for reading newspaper news and structured interviews Analyze the data by distributing the frequency. The results of the study showed that 1) the state of Thai social crisis from the violation of the Five Also has a violent classification The most violations of alcohol, drugs and intoxication (5th precepts), followed by life and physical violations (precepts 1), property violations (precepts number 2), verbal violations (precepts 4), and Sexual abuse and harassment (precepts number 3), respectively 2) causes of the crisis in Thai society from the violations of the Five precepts, it was found that 1) the abuse of life and the body (precepts number 1) caused by stress and personal problems 2) Property infringement (precepts number 2) was caused by advertising of convincing products for money from consumers, 3) sexual harassment (precept number 3), caused by pornography, widespread and accessible to all groups of people. 4) Verbal Abuse (Precept No. 4) Caused by the use of words that are harsh, sarcastic and rude to the cause of controversy 5) The abuse of alcohol, drugs and intoxication (Precept No. 5) is caused by stress. And easy access to distribution sources.